High fat diet causes inferior vertebral structure and function without disc degeneration in RAGE‐KO mice. Issue 7 (21st October 2021) - D'Erminio, Danielle N.; Krishnamoorthy, Divya; Lai, Alon; Hoy, Robert C.; Natelson, Devorah M.; Poeran, Jashvant; Torres, Andrew; Laudier, Damien M.; Nasser, Philip; Vashishth, Deepak; Illien‐Jünger, Svenja; Iatridis, James C.
Abstract: Back pain and spinal pathologies are associated with obesity in juveniles and adults, yet studies identifying causal relationships are lacking and none investigate sex differences. This study determined if high fat (HF) diet causes structural and functional changes to vertebrae and intervertebral discs (IVDs); if these changes are modulated in mice with systematic ablation for the receptor for advanced glycation endproducts (RAGE‐KO); and if these changes are sex‐dependent. Wild‐type (WT) and RAGE‐KO mice were fed a low fat (LF) or HF diet for 12 weeks starting at 6 weeks, representing the juvenile population. HF diet led to weight/fat gain, glucose intolerance, and increased cytokine levels (IL‐5, MIG, and RANTES); with less fat gain in RAGE‐KO females. Most importantly, HF diet reduced vertebral trabecular bone volume fraction and compressive and shear moduli, without a modifying effect of RAGE‐KO, but with a more pronounced effect in females. HF diet caused reduced cortical area fraction only in WT males. Neither HF diet nor RAGE‐KO affected IVD degeneration grade. Biomechanical properties of coccygeal motion segments were affected by RAGE‐KO but not diet, with some interactions identified. In conclusion, HF diet resulted in inferior vertebral structure and function with some sex differences, no IVD degeneration, and few modifying effects of RAGE‐KO. These structural and functional deficiencies with HF diet provide further evidence that diet can affect spinal structures and may increase the risk for spinal injury and degeneration with aging and additional stressors. Back pain and spinal pathologies are associated with obesity in juveniles and adults, yet studies identifying causal relationships are lacking and none investigate sex differences. Abstract : High fat (HF) diet led to obesity and inferior vertebral trabecular bone structure and function in mice of both sexes with greater effects in females. HF diet did not result in intervertebral disc degeneration in either sex but did cause inferior vertebral cortical bone structure in males. Systemic ablation of the receptor for advanced glycation endproducts (RAGE‐KO) had few modifying effects. These early structural deficiencies may increase risk for spinal injury and degeneration with aging and additional stressors.